Dramatic changes in the carbonate-hosted barium isotopic compositions in the Ediacaran Yangtze Platform. (15th April 2021) - Wei, Wei; Zeng, Zhen; Shen, Jun; Tian, Lan-Lan; Wei, Guang-Yi; Ling, Hong-Fei; Huang, Fang
Abstract: Barium (Ba) isotopic compositions (δ 138 Ba) have been advocated as a novel paleo-productivity proxy, because of the strong control of biological productivity on the distribution of the Ba isotopic composition in the modern oxic oceans. However, the ocean was dominantly anoxic throughout the majority of the Earth's history, and the biogeochemical cycle of Ba in anoxic oceans may have been different from the case in oxic ones. It is not clear whether δ 138 Ba can be used to trace biological productivity in ancient oceans. The Ediacaran Period was marked by a dramatic evolution in the climate, atmospheric and oceanic oxygen level, marine carbon cycle, and biosphere, which have been documented in multiple successions of the Ediacaran sedimentary rocks. This provides an opportunity to investigate variations in biogeochemical Ba cycle during the crucial period. In this study, we find large δ 138 Ba variations in carbonate rocks from the Ediacaran Doushantuo and Dengying Formations in the Yangtze Gorges area, South China. We suggest that detrital contamination and potentially post-depositional alteration cannot explain the δ 138 Ba variations. The post-Marinoan carbonate rocks record generally negative carbonate-hosted δ 138 Ba (δ 138 Bacarb ) around −0.3‰, reflecting the existence of a replete and homogeneous reservoir of light Ba isotopes in the postglacial ocean. Although the Shuram/Wonoka correlative carbonate rocks have documented a prominent negative δ 13 Ccarb excursion, the δ 138 Bacarb merely shows minor fluctuations between 0.00‰ and 0.35‰, possibly due to local anoxia/euxinia inhibiting the biogeochemical cycle of Ba. The late-Ediacaran carbonate rocks show a gradual increase in δ 138 Bacarb systematically with enhanced negative cerium anomalies, suggesting the establishment of the modern-ocean-like cycle of Ba in shallow waters of the Yangtze Platform, which may result from the replacement of cyanobacteria by eukaryotic macroalgae as the dominant primary producer. We suggest that the biogeochemical Ba cycle in ancient marine system is strongly controlled by local redox conditions, and thus Ba isotopic compositions could be utilized to trace variations in paleo-productivity, especially in oxic environments.